Genetic association of apolipoprotein E genotype with EEG alpha rhythm slowing and functional brain network alterations during normal aging - Ponomareva, Natalya V.; Andreeva, Tatiana V.; Protasova, Maria; Konovalov, Rodion N.; Krotenkova, Marina V.; Kolesnikova, Ekaterina P.; Malina, Daria D.; Kanavets, Elena V.; Mitrofanov, Andrey A.; Fokin, Vitaly F.; Illarioshkin, Sergey N.; Rogaev, Evgeny I. (Frontiers in Neuroscience, 2022)
The ε4 allele of the apolipoprotein E (APOE4+) genotype is a major genetic risk factor for Alzheimer’s disease (AD), but the mechanisms underlying its influence remain incompletely understood. The study aimed to investigate the possible effect of the APOE genotype on spontaneous EEG alpha characteristics, resting-state functional MRI (fMRI) connectivity (rsFC) in large brain networks and the interrelation of alpha rhythm and rsFC characteristics in nondemented adults during aging. We examined the EEG alpha subband’s relative power, individual alpha peak frequency (IAPF) and fMRI rsFC in nondemented volunteers (age range 26-79 years) stratified by the APOE genotype. The presence of the APOE4+ genotype was associated with lower IAPF and lower relative power of the 11-13 Hz alpha subbands. The age related decrease in EEG IAPF and relative power of 10-12 Hz frequencies were more pronounced in the APOE4+ than in the APOE4+ noncarriers (APOE4-). The APOE4+ carriers had a stronger fMRI positive rsFC of the interhemispheric regions of the frontoparietal, lateral visual and salience networks than the APOE4- individuals. In contrast, the negative rsFC in the network between the left hippocampus and the right posterior parietal cortex was reduced in the APOE4+ carriers compared to the noncarriers. Alpha rhythm slowing was associated with the dysfunction of hippocampal networks. Our results show that in adults without dementia APOE4+ genotype is associated with alpha rhythm slowing and that this slowing is age-dependent. Our data suggest predominant alterations of inhibitory processes in large-scale brain network of nondemented APOE4+ carriers. Moreover, dysfunction of large-scale hippocampal network can influence APOE-related alpha rhythm vulnerability.